2014
DOI: 10.17487/rfc7176
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Interconnection of Lots of Links (TRILL) Use of IS-IS

Abstract: The IETF Transparent Interconnection of Lots of Links (TRILL) protocol provides optimal pair-wise data frame forwarding without configuration in multi-hop networks with arbitrary topology and link technology; it also provides support for multipathing of both unicast and multicast traffic. This document specifies the data formats and code points for the IS-IS extensions to support TRILL. These data formats and code points may also be used by technologies other than TRILL. This document obsoletes RFC 6326.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 12 publications
0
48
0
Order By: Relevance
“…(Both the Port ID of the port on which a TRILL Hello is sent and the nickname of the sending TRILL switch appear in the Special VLANs and Flags sub-TLV [RFC7176] in TRILL IS-IS Hellos.) The resulting MAC address has the Local bit on and the Group bit off [RFC7042].…”
Section: +-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-mentioning
confidence: 99%
“…(Both the Port ID of the port on which a TRILL Hello is sent and the nickname of the sending TRILL switch appear in the Special VLANs and Flags sub-TLV [RFC7176] in TRILL IS-IS Hellos.) The resulting MAC address has the Local bit on and the Group bit off [RFC7042].…”
Section: +-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-+-mentioning
confidence: 99%
“…The Routing Bridge (RBridge) having the highest tree root priority announces the total number of trees that should be computed for the campus. It may also specify the list of trees that RBridges need to compute using the Tree Identifiers (TREE-RT-IDs) sub-TLV [RFC7176]. Every RBridge can specify the trees it will use for multi-destination TRILL Data packets it originates in the Trees Used Identifiers (TREE-USE-IDs) sub-TLV [RFC7176], and the VLANs or Fine-Grained Labels (FGLs) [RFC7172] it is interested in are specified in Interested VLANs and/or Interested Labels sub-TLVs [RFC7176].…”
Section: Background Descriptionmentioning
confidence: 99%
“…It may also specify the list of trees that RBridges need to compute using the Tree Identifiers (TREE-RT-IDs) sub-TLV [RFC7176]. Every RBridge can specify the trees it will use for multi-destination TRILL Data packets it originates in the Trees Used Identifiers (TREE-USE-IDs) sub-TLV [RFC7176], and the VLANs or Fine-Grained Labels (FGLs) [RFC7172] it is interested in are specified in Interested VLANs and/or Interested Labels sub-TLVs [RFC7176]. It is suggested that by default the ingress RBridge uses the distribution tree whose root is the closest [RFC6325].…”
Section: Background Descriptionmentioning
confidence: 99%
See 2 more Smart Citations